Comparing the effects of saffron, lippia, and saffron-lippia combination on anxiety among candidates for coronary angiography - Kobra Soheilipur; Mohammad Reza Khazdair; Seyyed Ali Moezi; Gholamhossein Mahmoudirad (Mashhad University of Medical Sciences, 2021)
Objective: Coronary artery disease (CAD) is among the most prevalent diseases in the world, and its severity is usually assessed through coronary angiography (CA). Anxiety is the most prevalent problem before angiography. The aim of this study was to evaluate Crocus sativus (saffron) and Lippia citriodora Kunth (lippia) extracts and saffron-lippia extract combination on anxiety among the candidates for CA. Materials and Methods: This double-blind randomized placebo-controlled trial in four month was conducted on 120 angiography candidates in Valiasr hospital, Birjand, Iran. The random allocation was doing through block randomization to saffron, lippia, saffron-lippia, and placebo groups; four hours before angiography, participants in these groups respectively received a single dose of saffron extract capsule (40 mg), lippia extract capsule (40 mg), saffron-lippia extract capsule (20 mg saffron and 20 mg lippia), and lactulose capsule (40 mg). Participants' anxiety was assessed before, thirty minutes after, and three hours after the intervention via Spielberger State-Trait Anxiety Inventory. Results: The mean scores of state, trait, and total anxiety in the saffron group reduced significantly (p <0.05), while the mean scores in the other groups did not change significantly, except for the mean score of trait anxiety in the saffron-lippia group which decreased significantly (p=0.05). Therefore, after the intervention, the mean scores of state, trait, and total anxiety in the saffron group were significantly lower than the other groups (all, p <0.05). Conclusion: This study suggests that the oral use of a single-dose of 40 mg saffron extract is effective in alleviating anxiety among the candidates for CA.